Assessment of the condition of Balsam poplar trees (Populus balsamifera L.) in a residental area of Bratsk - Runova, Elena (Acta silvae et ligni, 2021)
In this study, we investigated the health status of balsam poplar (Populus balsamifera L.) trees in a residential area of the city of Bratsk (Irkutsk Oblast, Russia). Visual and instrumental assessment of the health status of pruned and unpruned trees was performed. The identified internal defects in the tree were analyzed with a Resistograph device, which enabled the extent of decayed wood to be determined. Visual analysis revealed various types of damage: dried branches, brittle crowns, frost cracks, mechanical damage, curvature of trunks, decay and inclusions of foreign bodies. We compared trees with and without canopy pruning. We found that pruned trees were significantly more damaged than non-pruned trees. Decomposing wood at different stages of development was found in all the trees studied. A tree passport combining the visual and instrumental assessment data was compiled for each tree. The results of the research were used to formulate conclusions and recommendations for improving the management of urban trees in order to restore their ecological and aesthetic functions.
Keywords: decay; les; Populus balsamifera L.; razkroj; Resistograph; rezistograf; urban area; urbano področje; visual analysis; vizualna analiza; wood